(untitled) (Pedagogy of Higher and Secondary Education, 2012)
Lukyanik L. Kompetentnosny approach to the study of the Ukrainian language. The article is dedicated to the clarification of ways of management that influence the education of future teachers as for forming pupils’ communicative competence in the circumstances of using the competence approach.